REGIONAL CHARACTERISTICS AND HEALTH IMPACT OF OBESITY AMONG CHILDREN AND ADOLESCENTS IN UZBEKISTAN (American Journal of Interdisciplinary Research and Development, 2024)
Currently, the prevalence of overweight and obesity has acquired epidemic proportions. There are about 250 million people worldwide suffering from obesity, which accounts for 7% of the total adult population. WHO experts predict an almost twofold increase in the number of obese individuals by 2025 compared to the data from 2000, representing 45-50% of the adult population in the USA, 30-40% in Australia and the UK, and over 20% of the population in Brazil. In light of this, obesity has been recognized by WHO as the new non-communicable "epidemic" of our time (1, 2, 3). The obesity epidemic represents one of the most pressing public health problems in the WHO European region. Over the past two decades, obesity prevalence rates have nearly tripled. In WHO's European region countries, half of the adult population and every fifth child are overweight, and a third of them already suffer from obesity, with the number of such individuals rapidly increasing. Approximately 30% of the global population, or over 2 billion people, are overweight, and if current obesity growth rates persist, by 2030 it is expected that 70% of the world’s population will be overweight. Each year, diseases related to excess body weight cause more than one million deaths in the region (4,5).